Reservoir Characteristics for Khasib Formation in selected wells of East Baghdad Oil field, Iraq - Tukkee, Israa Qasem Hussain; Hussain, Salah Ali; Sahaab, Abdalratha Mohammed (Iraqi Journal of Science, 2023)
Four subsurface sections and electrical, porosity logs, and gamma-ray logs of the Khasib Formation (age Late Turonian-Lower Coniacian) were studied to identify reservoir characteristics and to evaluate the reservoir properties of the Khasib reservoir units in the East Baghdad oilfield. The lithology of the formation is limestone throughout the whole sequence in all studied wells EB-83, EB-87, EB-92, and EB94. It is bounded conformably from the top by Tanuma Formation and has a conformable lower contact with Kifl Formation. The lower and upper boundaries of the formation were determined using well log analysis, and the formation was divided into three main rock units (Kh1, Kh2, and Kh3), depending on the porosity logs. The porosity was calculated using acoustic or sonic, neutron, and density logs. The effective porosity (average 0.0 - 0.32 %) is the predominant porosity in the formation and to less extent; the secondary porosity. The volume of shale is very low (average 0.0 - 0.13 %), indicating limestone is the main rock of the Khasib Formation. The study of the reservoir water (average 0.11- 1.0%) and hydrocarbon saturations (average 0.0 - 0.88 %) showed that the formation contains varying proportions and quantities of water and hydrocarbons suspended in the wall void, and hydrocarbons capable of being produced. The lithological study reflected that the predominant lithic formation is limestone. It was found that Kh 2 unit is the best oil reservoir unit in all selected wells in terms of porosity, water saturation, diagenesis processes, and microfacies analysis.